Assessment of microbiological quality of khoa Based sweets marketed in Thrissur city - K. Radha; M. S. Salumol; C.T. Sathian (Indian Journal of Veterinary and Animal Sciences Research, 2023)
Bacteriological quality of khoa based sweets marketed through different retail outlets of Thrissur city was evaluated based on total viable count, coliform count, yeast & mould count and staphylococcal count. Altogether 72 samples of khoa based sweets such as peda, burfi and gulabjamun were evaluated for their bacteriological quality. Out of the total peda samples tested, coliforms were prevalent in 37.5%, yeast and mould in 91.7% and staphylococcal organisms in 41.7% of the samples. In burfi, coliforms were prevalent in 66.6%, yeast and mold in 95.8% and staphylococcal organisms in 83.3 % of the samples tested. In gulabjamun, coliforms, yeast and mould and staphylococcal organisms were present in 45.8%, 91.6% and 70.8% respectively of the samples tested. The highest rate of contamination was recorded in burfi while the lowest was recorded in peda. Strict hygienic measures during preparation and storage are recommended to ensure the quality of the products.